2013
DOI: 10.5535/arm.2013.37.1.41
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship Between Gross Motor Function and Daily Functional Skill in Children With Cerebral Palsy

Abstract: ObjectiveTo investigate the relationship between gross motor function and daily functional skill in children with cerebral palsy (CP) and to explore how this relationship is moderated by the Gross Motor Function Classification System, Bimanual Fine Motor Function (BFMF), neuromotor types, and limb distribution of CP.MethodsA cross-sectional survey of 112 children with CP (range, 4 years to 7 years and 7 months) was performed. Gross motor function was assessed with the Gross Motor Function Measure-66 (GMFM-66) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
2
8
0
1
Order By: Relevance
“…The social functioning domain is influenced by various factors such as education, socioeconomic status, cognition, communication abilities and motor function. 27 The opportunity to use or practice communication, listening and language skills during hippotherapy may have resulted in the improvements observed in PEDI social functioning, in line with Casady and Nichols-Larsen's 11 report.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The social functioning domain is influenced by various factors such as education, socioeconomic status, cognition, communication abilities and motor function. 27 The opportunity to use or practice communication, listening and language skills during hippotherapy may have resulted in the improvements observed in PEDI social functioning, in line with Casady and Nichols-Larsen's 11 report.…”
Section: Discussionsupporting
confidence: 56%
“…These findings suggest some positive effects of hippotherapy on the child's actual performance in daily life. The mobility domain is closely related to gross motor function based on GMFCS level, 27 while the self-care domain is related to both GMFCS level and hand function based on Manual Ability Classification System score. 28 According to a previous report, hippotherapy improved dynamic trunk stability and functional reach in children with spastic diplegia.…”
Section: Discussionmentioning
confidence: 99%
“…The children and adolescents at the institution had severe impairments in fine hand use (d440), compromising activities such as toileting (d530) and eating (d550). In fact, for Kwon, Yi, Kim, Chang, Kwon 34 and Brandão, Ocarino, Bueno, Mancini 41 , hand use in CP is strongly related to self-care. Experimental studies with rats have shown that hand use increases the flow of nerve impulses in the dendrites, with remodeling of neuronal circuits after fine motor stimuli 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Essa relação entre melhor GMFCS e desempenho funcional é esperada, na existência de padrões cognitivos semelhantes, e assim apresentam melhor repertório funcional em atividades de vida diária 14,17 Com as curvas fornecidas por Rosenbaum et al 18 Crianças com PC, quando comparadas com às típicas, apresentam mais dificuldade em atividades que envolvem características específicas de função manual (como função bimanual) como colocar e retirar roupa, abotoar e desabotoar, dentre outras), com dificuldades também no controle postural para executar tais atividades [22][23][24] .…”
Section: Resultsunclassified